2009
DOI: 10.1111/j.1365-2230.2008.03165.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological factors and serum zinc, folate and vitamin B12levels in the aetiology of trichodynia: a case-control study

Abstract: Trichodynia is a commonly encountered symptom in patients with diffuse alopecia, and depression and somatoform dissociation disorders may play an important role in its aetiology. Our data provide no evidence that serum levels of zinc, folate or vitamin B(12) are involved in the pathogenesis of trichodynia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…suggested depressive and somatoform disorders may play an important role in the etiology of trichodynia, in contrast to another study in which anxiety was not elevated in trichodynia patients. [22] The cause of this contradiction might be that unlike our study, the previous studies had taken the healthy subjects as control group.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…suggested depressive and somatoform disorders may play an important role in the etiology of trichodynia, in contrast to another study in which anxiety was not elevated in trichodynia patients. [22] The cause of this contradiction might be that unlike our study, the previous studies had taken the healthy subjects as control group.…”
Section: Discussionmentioning
confidence: 70%
“…Serum vitamin B12, ferritin, folate, and zinc levels were studied in only one trichodynia study previously. [22] Similar to Durusoy et al ., we found the serum levels of vitamin B12, ferritin, folate, TSH, and zinc were no different in the trichodynia and control patients. Also, similar to our study, Durusoy et al .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Painful hair sensations, discomfort and/or paraesthesia are known as trichodynia and have been reported to be associated with higher pain perception and possible psychological comorbidity . Trichodynia symptoms are of great relevance to patients and place the physician in a challenging diagnostic and therapeutic situation …”
Section: Introductionmentioning
confidence: 99%
“…It has been found that 76% of the people who had trichodynia had psychopathic signs versus 20% in the control group, supporting this idea. Researchers have observed and speculated that there is a connection between psychopathologic indings (such as anxiety) and trichodynia [1,5,6,[11][12][13][14]. In 2006 Gupta and Gupta.…”
Section: Ethiopathologymentioning
confidence: 99%